Conventional for drainage installation system at UMT education complex project / Muhamad Qadri Hidayat Abdul Kahar - Abdul Kahar, Muhamad Qadri Hidayat (Universiti Teknologi MARA UiTM,Perak, 2022)
The title of this project is ‘Conventional for Drainage Installation System at UMT Education Complex Project, Campus Bukit Kor, Lot 61108, Mukim Rusila, Daerah Marang, Terengganu Darul Iman’. This project is carried out on an area with base area of 600.70 acre (243.10 hectares). The terrain of the site area is hilly and also have lowlands and valleys area. The highest point of the project area is 120.19 meters and the lowest point is 3.90 meters from sea level. UMT Campus Bukit Kor located at Marang district, about 6 kilometers from city of Marang and 20 kilometers from city of Kuala Terengganu.This project is constructed by the main contractor, Sulong Engineering Sdn. Bhd. It consists of 4 level admin block, 1 level of college block and other support blocks with works around the building. Towards sustainable development, 1/3 from site area will be used for construction of UMT Campus Bukit Kor and the remaining 2/3 of site area will be maintained naturally. In a nutshell, this project consists of construction of buildings and infrastructures.